Implementasi Kebijakan Pendidikan Islam Di Lembaga Pendidikan Formal: Tantangan Dan Strategi Optimalisasi - Audiya, Saskia Wanda; Sabrifha, Eli (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2026)
This study aims to analyze the dynamics of Islamic education policy implementation in formal educational institutions and formulate optimization strategies using a descriptive qualitative approach and library research methods. The results indicate that the main challenges include curriculum dualism, teacher pedagogical competence, and limited managerial innovation. Optimization strategies focus on integrating the values of religious moderation, digital transformation, and visionary leadership. This study concludes that synchronizing policy and practice requires cross-sectoral collaboration that adapts to the dynamics of the times.